Potential misinformation in websites on carpal tunnel syndrome - Ria Goyal; Grace Corrier; David Ring; Amirreza Fatehi; Sina Ramtin (PEC Innovation, 2024)
Objective: We sought to evaluate the potential reinforcement of misconceptions in websites discussing carpal tunnel syndrome (CTS). Methods: After removing all cookies to limit personalization, we entered “carpal tunnel syndrome” into five search engines and collected the first 50 results displayed for each search. For each of the 105 unique websites, we recorded publication date, author background, and number of views. The prevalence of potential reinforcement and/or reorientation of misconceptions for each website was then scored using a rubric based on our interpretation of the best current evidence regarding CTS. The informational quality of websites was graded with the DISCERN instrument, a validated tool for assessing online health information. Results: Every website contained at least one potentially misleading statement in our opinion. The most common misconceptions reference “excessive motion” and “inflammation.” Greater potential reinforcement of misinformation about CTS was associated with fewer page views and lower informational quality scores. Conclusions: Keeping in mind that this analysis is based on our interpretation of current best evidence, potential misinformation on websites addressing CTS is common and has the potential to increase symptom intensity and magnitude of incapability via reinforcement of unhelpful thoughts regarding symptoms. Innovation: The prevalence of patient-directed health information that can increase discomfort and incapability by reinforcing common unhelpful thoughts supports the need for innovations in how we develop, oversee, and evolve healthy online material.